Dampak Penertiban Saham Publik Terhadap Penurunan Harga Saham - Farah Margaretha .; Puspa Ayu . (Jurnal Manajemen Maranatha, 2009)
This research aims to see the effect of Initial Public Offering to the long-run underperformance of IPO at compaines in Indonesia Stock Exchange (IDX). 1995 up to 2004. The data has been selected using a purposive sampling method. The independent variables are size of the firm (asset before the floatation and funds), quality of the firm (cost), risk of the firm (age and profitable before the floatation), reputation of the firm (sponsor), and agency costs after the IPO (equity of issue). While the dependent variables in this research are long-run underperformance of IPO seen in Market-Adjusted Buy and Hold Return (MABHR). The method used for data analysis are the ordinary least square. Based on the result of the whole research, it can be summarized that IPO and long-run underperformance have significance relationship.Keywords: Initial Public Offering (IPO), stock price, agency cost